Exergoeconomic analysis of a cogeneration plant in an iron and steel factory - KARACA ALBAYRAK, FATMA (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Cogeneration involves the production of both electricity and thermal energy generally in the form of steam or hot water, and it has a great potential of saving primary energy in comparison to separate generation technologies. The use of cogeneration provides high energy conversion efficiency, and it also lowers the emissions released to the environment. Exergy analysis is an effective tool which provides insights into the performance of energy conversion systems, and highlights the possible improvements. On the basis of exergy concept and economics, an exergoeconomic analysis provides useful information to understand the behaviour of an energy conversion system from the cost viewpoint. This study presents the exergoeconomic analysis of a cogeneration plant at ERDEMIR, TURKEY. The mass, energy and exergy balances were done, and the exergoeconomic analysis of the plant with a 39.5 MW electricity and 80 ton/h steam production capacity, was performed. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Exergy; Exergoeconomics; Cogeneration; Simulation; EXERGY ANALYSIS; COMBINED HEAT; POWER-PLANT; ENERGY; CYCLE